1982
DOI: 10.1073/pnas.79.9.3037
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonic acid in human plasma: relationship of concentration and circadian rhythm to cholesterol synthesis rates in man.

Abstract: We tested the hypothesis that the rate of cholesterol synthesis in tissues determines the concentrations of mevaIonic acid (MVA) in plasma. We found that plasma MVA concentrations were correlated (i) with increased rates of whole-body cholesterol synthesis (measured by sterol-balance methods) in patients treated with cholestyramine resin and (ii) with decreased rates of whole-body sterol synthesis (indicated by conversion of labeled acetate to sterol in freshly isolated mononuclear leukocytes) in out-patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 19 publications
3
83
1
1
Order By: Relevance
“…(19), as modified by Parker et a1. (20). Attempts to analyse postprandial samples for mevalonic acid proved to be impractical because of the presence in the plasma of substances that interfered with the measurement.…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…(19), as modified by Parker et a1. (20). Attempts to analyse postprandial samples for mevalonic acid proved to be impractical because of the presence in the plasma of substances that interfered with the measurement.…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…5) Despite the importance of HMG-CoA reductase inhibitors in the management of dyslipidemia, the relationship between drug exposure and the extent of HMG-CoA inhibition has not been elucidated. In general, peak cholesterol biosynthesis occurs at night, 6) suggesting that the hypocholesterolemic effects of HMG-CoA reductase inhibitors are stronger after evening administration than after morning administration. However, robust trials are necessary to determine the best administration time to achieve optimal LDL-C lowering for rosuvastatin.…”
mentioning
confidence: 99%
“…Studies in our laboratory and others have shown that changes in the concentrations of mevalonate in plasma and urine reflect parallel changes in the activity of hepatic HMG-CoA reductase and thus normally reflect changes in the rates of whole body cholesterol biosynthesis (22)(23)(24)(25). While plasma concentrations of mevalonic acid exhibit diurnal variations with peak values occurring at night (25)(26)(27), the mean 24-h plasma concentration is an accurate indicator of the rates of hepatic (whole body) cholesterol synthesis under different metabolic conditions. The 24-h urinary excretion of mevalonate reflects the integrated plasma concentration and provides a more practical and non-invasive way of assessing whole body cholesterol synthesis.…”
mentioning
confidence: 99%